Experiments on Air Compression with an Isothermal Piston for Energy Storage - Teng Ren; Weiqing Xu; Maolin Cai; Xiaoshuang Wang; Minghan Li (Energies, 2019)
Air is usually compressed adiabatically in the compressor. As the operating speed of compressors can be several thousand rpm, heat generated during compression cannot be sufficiently transmitted to the environment in such a short time. It is for this reason that compressor efficiency is limited. Isothermal compression could be an alternative choice applied on industrial compressor and compressed air energy storage (CAES). This paper proposed a new kind of piston to perform isothermal compression. Surface area of such isothermal piston structure is larger. A certain amount of fluid at the chamber bottom absorbs the heat from the isothermal piston. Heat transfer between piston and fluid during compression is investigated. Air pressure is measured to validate the effectiveness of this proposed piston structure in heat transfer. Compression work of the proposed isothermal piston and conventional one is compared. One issue of this comparison is that air-liquid dissolution can affect the pressure and compression work. The influence of dissolution is quantified with Henry’s Law. Quantitative analysis is performed to determine that heat transfer is the dominant factor affecting the pressure and compression work. Some simple experiments are described in this paper, which shed light on that heat transfer could be significantly improved adopting this proposed isothermal piston.